Strategi Media Sosial Marketing untuk Produsen Kerupuk Bawang Rejo Agung: Membangun Ekonomi dalam Bingkai Pancasila - Anwar, Joni; Sumantri, Imam; Julia, Celsa; Khoerunisa, Arina Zahro (Yayasan Daarul Huda Kruengmane, 2025)
Susukan Village, Semarang Regency, has economic potential through the “Paguyuban Rejo Agung” onion cracker home industry in Ketanggen Hamlet. Although it has a positive impact on the village economy, product marketing is still limited to conventional methods (offline) due to a lack of understanding of digital marketing. Semarang State University (UNNES) KKN students GIAT 11 held digital marketing training for members of Paguyuban Rejo Agung. This training includes the use of digital platforms such as Shopee, TikTok, Instagram, and Facebook, as well as content editing applications such as CapCut and Canva. The training was carried out in three meetings, including application introduction, creative content creation, and hands-on practice. As a result, participants showed high enthusiasm and increased skills in digital marketing. This activity also reflects the values of the 4th principle of Pancasila, namely “People’s Republic led by the wisdom of wisdom in deliberation/representation,” where decisions are made through deliberation and mutual cooperation to reach a joint agreement for the advancement of the community’s economy. This training is expected to expand the reach of product marketing, increase production efficiency, and contribute to village economic growth.